The Legal Status of Church-State Relationships in the United States : With Special Reference to the Public Schools - Johnson, Alvin W. (Alvin Walter), 1895-1958 (Book collections on Project MUSE., 1934)
The Legal Status of Church-State Relationships in the United States was first published in 1934. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.